Ethical Leadership as a Discouragement Agent for Moral Disengagement and Unethical Behaviour in Cross-Cultural Environment - Alvez, Marlond Moored Antunez (2021)
Since the huge corporate scandals that impacted the world, authors keep reviewing concepts trying to identify what is missing on the ethical behaviour of managers, leaders and top executives in multinational corporations. Drawing on the Social Cognitive Theory of Bandura that explains the psychological aspect of the individuals and social interaction given by the ethical climate, we propose that ethical leadership downhearted individual’s moral disengagement preventing teams to behave unethically in cross-cultural environment. We empirically tested this theoretical framework by collecting data from 184 participants comprised in 39 teams across countries, prompted to answer a multi-source survey in dyads and in two different moments of time. The findings reveal that ethical leadership has an indirect influence on unethical behaviour avoidance by stimulating a good ethical climate and frustrating the moral disengagement of individuals. In addition, could be proved that organization ethical climate is not influenced by the corruption level of the country. All these findings offer theoretical and managerial implications that transcend the simply view of the ethical leader as a good manager, to a broader view of the ethical leader as an asset of the organization that not only improves ethics, but also performance and societal recognition.